CTE 2019 - When cloud technologies ruled the education - Arnold E. Kiv; Mariya P. Shyshkina; Serhiy O. Semerikov; Andrii M. Striuk; Mykola I. Striuk; Hanna M. Shalatska (Academy of Cognitive and Natural Sciences, 2020)
This is an introductory text to a collection of papers from the CTE 2019: The 7th Workshop on Cloud Technologies in Education, which was held in Kryvyi Rih, Ukraine, on the December 20, 2019. It consists of short introduction and some observations about the event and its future.